BLOCKCHAIN TECHNOLOGIES IN MANAGING SOCIOECONOMIC SYSTEMS: A STUDY OF LEGAL PRACTICE - Novikov, Aleksey; Gavrikov, Evgeny; Oleynik, Aleksandr; Zhirnov, Yuriy; Pestov, Nikolay (Revista Inclusiones, 2020)
The paper addresses the possibilities of adopting the blockchain technology in socioeconomic management in the context of digitalisation of the economy. On the cards in the near future in Russia is the expansion of the digital revolution, including the transition to a knowledge-based economy, digital technology, intellectual systems and robotics. However, a radical change of socioeconomic systems would require new approaches, principles and concepts. The paper aims to assess all advantages and disadvantages of the blockchain technology for adoption and application in socioeconomic management. The evolution of blockchain is discussed with a focus on blockchain 3.0 characteristics potentially valuable for organisational and managerial decision-making in socioeconomic design. Deficiencies of the regulatory framework hindering blockchain integration in this segment are pointed out. An analysis of international practice is provided based on the cases of introduction of the blockchain technology in public administration and public and municipal services. Conclusions are drawn concerning the possibility of adopting international practices on Russian soil. A concept is proposed taking into account the potential of designing management technologies for major socioeconomic systems. A crucial observation concerns the difficulties of integrating digital technologies into major complex socioeconomic systems, which not only complicates digitalisation but may be fraught with new problems in case of inappropriate simplification of virtual and real systems.